PATHWAYS TO RADICALISM: EXAMINING ONLINE COMMUNITY AND POLITICAL PATHWAYS TO MORE RADICAL BELIEFS ON REDDIT - Zulli, Diana; Mann, Marcus; Foote, Jeremy; Ku, Emily; Primm, Emily (AoIR Selected Papers of Internet Research, 2023)
Recent research shows that “algorithmic radicalization” and “echo chambers”—the idea that recommendation algorithms on social media have a strong independent effect on radicalization and silo people into ideologically homogeneous communities—are not as prevalent nor influential as once feared. Yet, online political discourse is as toxic as ever while political misinformation continues to plague social media platforms. This begs the question: If algorithms aren’t encouraging radicalization, then what is producing it? Drawing from church-sect theory, this study interviews politically active Reddit users to better understand _how_ they arrived at their current media use, online engagement, and political beliefs. Results show that participants have a deep mistrust of mainstream media, leading them to seek alternative sources of political content. Reddit participation is also driven by a desire for “earnest” political discussions with like-minded individuals and cross-partisans, in part to “reject” partisan polarization. Despite engaging on more extreme subreddits, participants said their beliefs were unchanged, but that other Redditors had moved to more extreme beliefs over time. And, participants perceived their Reddit participation as necessary to _prevent_ radicalization and partisan polarization. Collectively, these results provide preliminary insight into the media and social/psychological pathways that could lead to online radicalization, providing an alternative explanation to algorithmic radicalization. This study also underscores the importance of interrogating the ecological pathways to radicalization for researchers and policy-makers; future interventions should account for attribution bias and the individual-level factors related to radicalization.